Determination of freshness quality changes using selective methods: A comparative study for eclipse parrotfish (Scarus russelii) and spangled emperor (Lethrinus nebulosus) - Sutharshiny, S.; Shobana, C.; Sivashanthini, K. (University of Jaffna, 2021)
The present study was carried out to determine freshness quality and remaining storage time of eclipse parrotfish and spangled emperor stored in ice on days 0, 2, 3, 5, 7, 9, 12, 15, 19 and 21 using selective methods. A score of 11-12 coincided with the level at which the fish were considered unacceptable by a sensory panel of six experienced assessors. The demerit score of eclipse parrotfish and spangled emperor increased linearly (R2 =0.9563 and 0.9624, respectively) with storage time. The limit for acceptability of eclipse parrotfish and spangled emperor stored in ice was 9 and 19 days respectively. Total volatile base nitrogen value (45.87±1.10 mg/100g) for parrotfish stored in refrigerator exceeded limit of acceptability at the time of sensory rejection (9th day) while the value (5.93±0.28 mg/100 g) for spangled emperor was remained below the limit of acceptability after 9 days and increased to 54.96±1.80 mg/100g at the 19th day. The pH for both fishes showed significant (p<0.05) increases during the storage. Total viable count in spangled emperor analyzed were found to be below the acceptability limits (6 log10 cfu/g) by 15 days while maximum level of acceptability of eclipse parrotfish was until 7 days. Shelf-life of both fishes was different. Sensory score, value of TVB-N, pH and TVC provide evidence that the limit for acceptability was 7 days for eclipse parrotfish and 15 days for spangled emperor stored at 0 - 2 0C
Keywords: Eclipse parrotfish; ,Freshness quality; Spangled emperor